2012
DOI: 10.4103/2229-5186.99559
|View full text |Cite
|
Sign up to set email alerts
|

The bountiful biological activities of cyclotides

Abstract: Cyclotides are exceptionally stable circular peptides (28-37 amino acid residues) with a unique cyclic cystine knot (CCK) motif that were originally discovered through ethnobotanical investigations and bioassay-directed natural products screenings. They have been isolated from four angiosperm families (Violaceae, Rubiaceae, Curcurbitaceae, and Fabaceae), and they exhibit a wide range of bioactivities including antibacterial/antimicrobial, nematocidal, molluscicidal, antifouling, insecticidal, antineurotensin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…In contrast, vaby D (net charge -1) was isolated from Viola abyssinica which grows in extreme habitats and altitudes in the Ethiopian Highlands. The peptide was found to have a broad spectrum of anticancer activity with IC 50 values ranging between 3 μM to 47 μM when directed against a variety of cancers, including hepatocellular carcinoma cells (BEL-7402), and breast carcinoma (MDA-MB-231) [42,73]. More recently, the mechanisms underpinning the activity of the peptide to U-937 GTB lymphoma cells was investigated, which suggested that, in addition to targeting the membranes of these cells, the peptide may be taken up to inflict damage on DNA and other internal targets [74].…”
Section: Ahdps From Cyclotidesmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, vaby D (net charge -1) was isolated from Viola abyssinica which grows in extreme habitats and altitudes in the Ethiopian Highlands. The peptide was found to have a broad spectrum of anticancer activity with IC 50 values ranging between 3 μM to 47 μM when directed against a variety of cancers, including hepatocellular carcinoma cells (BEL-7402), and breast carcinoma (MDA-MB-231) [42,73]. More recently, the mechanisms underpinning the activity of the peptide to U-937 GTB lymphoma cells was investigated, which suggested that, in addition to targeting the membranes of these cells, the peptide may be taken up to inflict damage on DNA and other internal targets [74].…”
Section: Ahdps From Cyclotidesmentioning
confidence: 99%
“…4) [41][42][43], thereby giving the tertiary structure of these molecules amphiphilic characteristics that allow partitioning into biological bilayers [75,76]. However, based on structural differences in their molecular framework, cyclotides can be divided into a number of groups [41,42], including two major subfamilies, generally known as the Möbius and bracelet peptides (Fig. 4) [15,77], and a much smaller group termed chimeric cyclotides [65].…”
Section: Ahdps From Cyclotidesmentioning
confidence: 99%
See 3 more Smart Citations